Influence of the Martian crustal magnetic fields on the Mars-solar wind interaction and plasma transport - Li, Guokan; Lu, Haoyu; Li, Yun; Song, Yihui; Cao, Jinbin; Li, Shibang (Frontiers in Astronomy and Space Sciences, 2023)
The plasma transport process is important for the ionosphere of Mars, which controls the structure of the ionosphere above an altitude of 200 km. Plasma transport from the dayside ionosphere is crucial for producing the nightside ionosphere on Mars. The alteration in dayside plasma transport in the presence of crustal fields may influence the distribution of Martian ionospheric plasma and plasma escape in the magnetotail. This study employed a three-dimensional multispecies magnetohydrodynamic (MHD) model to simulate Mars-solar wind interactions. We show the magnetic field distribution and plasma velocity variation on the Martian day-side. The results indicate that the ion transport from low- to high-solar-zenith-angle areas in the south is inhibited by crustal fields, leading to a reduction in the ion number density and a thinner ionosphere near the southern terminator. Many heavy ions remain in the southern dayside ionosphere rather than moving to the nightside. In addition, the maximum reduction in the tailward flux of the planetary ions calculated by the MHD simulation is more than 50% at the southern terminator, indicating an inhibitory effect of the crustal fields on day-to-night transport. These effects may lead to a reduction in ion number density in the southern nightside ionosphere. Finally, we demonstrate a decrease in the global heavy-ion loss rate.